Uso do instrumento Elders Risk Assessment (ERA) para a predição de desfechos desfavoraveis em saúde de idosos - Barbosa, Cristian Dias (2016)
The study of predictors of health risk is important to assist professionals in the area in making clinical decisions at the individual or collective level. With focus on the elderly population, in 2005, the Elders Risk Assessment (ERA) was developed in Rochester, MN, USA. Its main advantage over other predictors is the practicality of use, since the data are obtained in an administrative way through the medical record review. Until now, this instrument has not been studied in Brazil. In this sense, this work was developed to use the ERA instrument as a predictor of risk of health problems in the elderly attended at the Hospital Universitário de Santa Maria, RS. The outcomes (events) considered for risk prediction were hospital admissions and urgent/emergency care. From the review of medical records, the ERA scores were obtained from a sample of 135 older adults seen outpatient in the year 2010 and the outcomes were surveyed between 2010 and 2012. Like the original study, the results showed a positive correlation between higher ERA scores and greater number of events. It is concluded that the ERA instrument can be used in our environment as a tool for risk screening for unfavorable events in the health of the elderly. It is also possible to characterize strategies of clinical approach in order to modify the tendency towards unfavorable outcomes. Considering the population cut and the study design chosen, other works are needed to prove the reproducibility of the instrument under different conditions, both in the public health system (SUS) and in the supplementary health.